"I'm gonna Spanglish it on you": Self-reported vs. oral production of Spanish–English codeswitching. Issue 2 (4th March 2020) - Cox, Jessica G.; LaBoda, Ashley; Mendes, Najee
Abstract: Much bilingualism research includes some consideration of codeswitching, which may be measured via self-report, an experimental task, or sociolinguistic interview; however, there is little triangulation across measures in either psycholinguistic or sociolinguistic approaches. To consider possible differences between self-report and oral production of codeswitching, Spanish–English bilinguals completed a codeswitching questionnaire and oral production in an autobiographical memory task. They also completed proficiency and executive function tests. We found that broad measures of self-reported and orally produced codeswitches were positively correlated, although relationships with proficiency and executive function were more complex. These findings may direct future studies' operationalization of codeswitching.